(untitled) (Scientific journal of the Fergana State University, 2024)
The article explores the benefits and priorities of using game technologies in the preparation of future educators studying in higher education institutions for professional activities on the basis of scientific approaches. The purpose of choosing a topic is to develop the ability of students of the preschool educational direction to organize quality education for children in the future by effectively preparing them for professional activities. The leading activity of a preschool child is considered as a game, focusing on the formation of the skills of future educators to be able to apply effective approaches to the organization of children’s activities in the future through the development of this competence. The use of gaming technologies in the implementation of these tasks shows an effective result. Playful education is considered an activity that is fun and without mental strain. The use of this direction in the educational system of students of preschool educational directions, provided that little attention is paid to this approach of education in higher educational institutions, is considered the most optimal way in understanding the content of the specialty. The results of the study show that the use of gaming technologies in lesson (lecture, practical, seminar) classes can make it possible to fully prepare the future preschool educator for professional activities. Therefore, instead of the conclusion in the article, the need to organize training in higher education on the basis of Game Technologies is given as a priority.